Chemical Structure of Lagochilin Diterpenoid (3,15,16,18-Tetrahydroxy 9-13 Epoxylab) From Lagochilus Inebrians Plant, Monohdrate AND Anhydrate Forms (The Peerian Journal, 2023)
In this article Lagochilin diterpenoid ( 3,15,16,18-tetrahydroxy 9-13 epoxylab) isolated from the plant Lagochilus inebrians Bge in the process of recrystallization in different solvents, lagoxilin crystals can be obtained in 2 different forms: the first form is monohydrate and the second form is non-hydrated, and lagoxilin mainly precipitates as monohydrate. The precipitated crystal has a monohydrate form and is completely insoluble in water information about the study of conditions is presented.